Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1016/j.carbon.2004.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Structural and chemical evolution of single-wall carbon nanotubes under atomic and molecular deuterium interaction

Abstract: The interaction of atomic (D) and molecular (D 2 ) deuterium, as present in a (D + D 2 ) gas mixture, with single-wall carbon nanotubes (SWNTs) has been studied by means of a combination of scanning electron microscopy, transmission electron microscopy and X-ray photoelectron spectroscopy. The SWNT samples were exposed to the gas mixture, produced by thermal dissociation of D 2 on a hot W filament, its temperature, T W , being kept at 1020 and 1550 K for a deuterium pressure of 0.6 and 60 Pa, respectively. Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 42 publications
(96 reference statements)
3
10
0
Order By: Relevance
“…TEM analysis (Figure 7) was performed for the samples shown in Figure 5a,b, i.e., CVD treated at 28.6 vol.% CH 4 for 30 and 150 s (silicon substrates). Figure 7a shows a typical structure of a CNTs bundle containing SWCNTs; the same bundle structure was reported in other works [34,35]. In the sample in Figure 7b, both single nanotubes (Figure 7 (1)) and CNTs bundles (Figure 7 dash line) can be observed, and at 30 s a distinct crystal structure could still be traced in CNTs.…”
Section: Tem Observationssupporting
confidence: 78%
See 1 more Smart Citation
“…TEM analysis (Figure 7) was performed for the samples shown in Figure 5a,b, i.e., CVD treated at 28.6 vol.% CH 4 for 30 and 150 s (silicon substrates). Figure 7a shows a typical structure of a CNTs bundle containing SWCNTs; the same bundle structure was reported in other works [34,35]. In the sample in Figure 7b, both single nanotubes (Figure 7 (1)) and CNTs bundles (Figure 7 dash line) can be observed, and at 30 s a distinct crystal structure could still be traced in CNTs.…”
Section: Tem Observationssupporting
confidence: 78%
“…In the Raman spectra maps (not presented), two typical spectra were observed; the spectrum of an evenly distributed network of carbon nanotubes (Figure 8a), and the spectrum of a high-density agglomerations of nanotubes (Figure 8b). Figure 7a shows a typical structure of a CNTs bundle containing SWCNTs; the same bundle structure was reported in other works [34,35]. In the sample in Figure 7b, both single nanotubes (Figure 7 (1)) and CNTs bundles (Figure 7 dash line) can be observed, and at 30 s a distinct crystal structure could still be traced in CNTs.…”
Section: Raman Observationssupporting
confidence: 78%
“…Of these five, the nanostructured carbon materials have sparked an increasing interest for chemists, physicists, and materials scientists worldwide . Because of their unique structural, mechanical, and electronic properties, there are numerous envisioned applications of nanostructured carbons including electrode materials for lithium ion batteries, gas storage media, catalyst supports, adsorbents, and electronic devices. However, a targeted production of carbon nanospheres (CNSs) is only now starting to achieve a significant research activity. Their high surface chemical activity provided by the unclosed graphitic layers, which provides reactive “dangling bonds”, makes them suitable materials for catalysis and adsorption processes.…”
Section: Introductionmentioning
confidence: 99%
“…When the H dose and H-atom exposure temperature is increased, irreversible structural changes to the CNT structure can begin. 18 For example, Zhang et al 12 observed that when plasma power or H-exposure time was increased, CNTs were cut and etched. Rao et al 19 found that SWCNTs were easily etched by H 2 at 900°C but remained unaffected at 800°C.…”
Section: Introductionmentioning
confidence: 99%